2020
DOI: 10.17713/ajs.v49i4.1142
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Dark Figure of COVID-19 Cases in Austria: Borrowing From the Decode Genetics Study in Iceland

Abstract: The number of undetected cases of SARS-CoV-2 infections is expected to be a multipleof the reported figures mainly due to the high ratio of asymptomatic infections and tolimited availability of trustworthy testing resources. Relying on the deCODE study inIceland, which offers large scale testing among the general population, we investigate themagnitude and uncertainty of the number of undetected cases COVID-19 cases in Austria.We formulate several scenarios relying on data on the number of COVID-19 cases which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…In Austria, which is a country that started testing at high proportions, the CFR value suggests that around than 25% of the infected individuals are tested. As a result, the total number of infected individuals is at least more than four times the total infected individuals tested, which coincides with the lower bound estimated by a recent study (25). We extend the analysis to the whole world, with results detailed in the supplementary materials (see Fig.…”
Section: Main Textsupporting
confidence: 90%
“…In Austria, which is a country that started testing at high proportions, the CFR value suggests that around than 25% of the infected individuals are tested. As a result, the total number of infected individuals is at least more than four times the total infected individuals tested, which coincides with the lower bound estimated by a recent study (25). We extend the analysis to the whole world, with results detailed in the supplementary materials (see Fig.…”
Section: Main Textsupporting
confidence: 90%
“…Interestingly, the incidence of SARS-CoV-2 positive cases in the investigated time period was lower in the Bavarian State Opera than in Bavaria and Germany, respectively. This is even more astounding since weekly up to 300 of 1,700 employees (17.6%) were tested at least once and thus testing frequency was much higher than that in overall Germany (maximum 0,5%) It is well known the real number of SARS-CoV-2 infections is up to 8.35 compared to the amount of tested people [39] and if the test frequency is elevated a higher incidence is expected. Over time, in 39 of 48 weeks, the estimated 7-day incidence per 100,000 employees of the Bavarian State Opera was lower than the respective 7-day incidence per 100,000 Bavarians, and in 23 weeks, no single case had been detected.…”
Section: Discussionmentioning
confidence: 97%
“…Estimations of number of undetected infections were rarely done so far. A study using data from Austria and Iceland found an almost similar factor of 8.35 [ 9 ], whereas a factor of 5 was determined in a hot spot area [ 8 ].…”
Section: Discussionmentioning
confidence: 99%